Smuggling or violation of customs rules: actual questions of application of administrative and criminal liability - Підгородинський, Вадим Миколайович; Підгородинський, В. М.; Подгородинский, Вадим Николаевич; Pidhorodynskyi, Vadym M.; Каменський, Дмитро Васильович; Каменський, Д. В.; Каменский, Дмитрий Васильевич; Kamenskyi, Dmytro V.; Kamensky, Dmitriy; Болокан, Інна Вікторівна; Болокан, І. В.; Болокан, Инна Викторовна; et al. (Universidad del Zulia, 2021)
The article deals with the peculiarities of the application of legal liability for commercial contraband in accordance with the current legislation of Ukraine. In particular, the authors of the article investigate the feasibility of criminalization of the smuggling of a wide range of goods, and not only withdrawn from the circulation of things and forests, as recorded in the Criminal Code of Ukraine at this moment. In addition to a thorough analysis of the current legislation of Ukraine, the authors carried out a comparative analysis of Ukrainian legislation with the legislation of foreign countries, which helped to objectively assess the state of the studied issues in Ukraine. The methodology of the study includes general scientific methods, among which the methods of analysis and synthesis should be noted, as well as special-legal methods, among which it is necessary to distinguish system-functional, and comparative methods. As a result of the study, the authors concluded that the criminalization of commercial smuggling (in connection with additional corruption risks and an increase in law enforcement agencies) is inappropriate. Thus, it is proposed to leave the current legislation of Ukraine in the investigational sphere in the current state and do not make any changes to it.

У статті розглядаються особливості застосування юридичної відповідальності за комерційну контрабанду відповідно до чинного законодавства України. Зокрема, автори статті досліджують доцільність криміналізації контрабанди широкого спектру товарів, а не лише вилучених з обігу речей та лісів, про що на цей момент зафіксовано в Кримінальному кодексі України. Окрім ґрунтовного аналізу чинного законодавства України, автори здійснили порівняльний аналіз законодавства України із законодавством зарубіжних країн, що допомогло об’єктивно оцінити стан досліджуваних питань в Україні. Методологія дослідження включає загальнонаукові методи, серед яких слід виділити методи аналізу та синтезу, а також спеціально-юридичні методи, серед яких необхідно виділити системно-функціональні, та порівняльні методи. У результаті дослідження автори дійшли висновку про недоречність криміналізації комерційної контрабанди (у зв’язку з додатковими корупційними ризиками та збільшенням правоохоронних органів). Таким чином, пропонується залишити чинне законодавство України у слідчій сфері в нинішньому стані та не вносити до нього жодних змін.
Pidgorodynskyi V. Smuggling or violation of customs rules: actual questions of application of administrative and criminal liability / V. Pidgorodynskyi, D. Kamensky, I. Bolokan, T. Makarenko, H. Samilo // Cuestiones Politicas. - Vol. 39. - Iss. 70. - Universidad del Zulia, 2021. - Р. 800-814.
Keywords: smuggling; crime; offense; customs rules; criminalization; контрабанда; злочин; правопорушення; митні правила; криміналізація; Research Subject Categories::LAW/JURISPRUDENCE